Seizure Susceptibility and Epileptogenesis in a Rat Model of Epilepsy and Depression Co-Morbidity - Epps, S Alisha (Nature Publishing Group, 2012)
Although a strong co-morbidity exists clinically between epilepsy and depression, the cause of this co-morbidity remains unknown, and a valid animal model is crucial for the identification of underlying mechanisms and the development of a screening tool for novel therapies. Although some rodent models of epilepsy have been reported to display behaviors relevant to affective disorders, the seizure susceptibility of animals prone to depression-like behavior has not been characterized. Toward this end, we assessed several forms of seizure sensitivity and epileptogenesis in rats selectively bred for vulnerability (Swim Lo-Active; SwLo) or resilience (Swim High-Active; SwHi) to depression-like phenotypes. The SwLo rats exhibit decreased motor activity in a swim test and other depression-like phenotypes, whereas the SwHi rats display increased motor activity in a swim test. SwLo rats exhibited a decreased latency to limbic motor seizures following acute pilocarpine administration in the absence of differences in pilocarpine pharmacokinetics, and also had a decreased threshold to tonic seizures induced by electroshock. Approximately half of the SwLo rats, but none of the SwHi rats, had spontaneous limbic motor seizures 5 weeks following pilocarpine-induced status epilepticus. While the number of stimulations required to achieve full amygdala and hippocampal electrical kindling were similar in the two rat lines, SwLo rats had a lower final hippocampal kindling threshold and more wet dog shakes during both amygdala and hippocampal kindling. Combined, these results indicate that SwLo rats are a model of epilepsy and depression co-morbidity that can be used for investigating underlying neurobiological and genetic mechanisms and screening novel therapeutics.